Electromagnetic interference from left ventricular assist devices detected in patients with implantable cardioverter‐defibrillators. (6th December 2021) - Sheldon, Seth H.; Jazayeri, Mohammad‐Ali; Pierpoline, Michael; Mohammed, Moghniuddin; Parikh, Valay; Robinson, Alexander; Noheria, Amit; Haglund, Nicholas; Sauer, Andrew J.; Reddy, Y. Madhu
Abstract: Introduction: Electromagnetic interference (EMI) from left ventricular assist devices (LVADs) can cause implantable cardioverter‐defibrillator (ICD) oversensing. We sought to assess the frequency of inappropriate shocks/oversensing due to LVAD‐related EMI and prospectively compare integrated (IB) versus dedicated bipolar (DB) sensing in patients with LVADs. Methods: Single‐center study in LVAD patients with Medtronic or Abbott ICDs between September 2017 and March 2020. We excluded patients that were pacemaker dependent. Measurements were obtained of IB and DB sensing and noise to calculate a signal‐to‐noise ratio (SNR). Device checks were reviewed to assess appropriate and inappropriate sensing events. Results: Forty patients (age 52 ± 14 years, 75% men, 38% ischemic cardiomyopathy) were included with the median time between LVAD implantation and enrollment of 6.7 months (2.3, 11.4 months). LVAD subtypes included: HeartWare ( n = 22, 55%), Heartmate II ( n = 10, 25%), and Heartmate III ( n = 8, 20%). Over a follow‐up duration of 21.6 ± 12.9 months after LVAD implantation, 5% of patients ( n = 2) had oversensing of EMI from the LVAD (both with HeartWare LVADs and Abbott ICDs) at 4 days and 10.8 months after LVAD implantation. Both patients underwent adjustment of ventricular sensing with resolution of oversensing and no further events over 5 and 15 months of further follow‐up. The SNR was similar between IB and DB sensing (50 [29–67] and 57 [41–69], p = 0.89). Conclusion: ICD oversensing of EMI from LVADs is infrequent and can be managed with reprogramming the sensitivity. There was no significant difference in the R‐wave SNR with IB versus DB ICD leads. Abstract : Electromagnetic interference in patients with left ventricular assist devices and implantable cardioverter‐defibrillators